2008
DOI: 10.1016/j.febslet.2008.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic effect of insulin on beta cell apoptosis depending on glucose deprivation

Abstract: Insulin resistant states are associated with an increase in the beta cell mass and also high levels of circulating insulin. Ultimately the beta cells undergo a failure that leads to diabetes. At this stage, a question arises if those persistent high levels of circulating insulin may contribute to beta cell damage. To address this important issue, we submitted beta cells to a prolonged effect of increasing concentrations of insulin. We observed that a prolonged effect of high levels of insulin on the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…This notion is consistent with previous findings that have shown that insulin can increase ROS levels in target cells (Goldstein et al 2005b), probably via the NOX family of NADPH oxidases (Guichard et al 2008), several members of which 230:3 are expressed in pancreatic islets (Guichard et al 2008). Insulin was also reported to induce apoptosis in glucosedeprived β cells (Guillen et al 2008) and potentiate the deleterious effects of H 2 O 2 on β cell survival (Sampson et al 2010). Of special interest in this regard is our finding that insulin increased the expression of iNos and Trb3, factors whose expression is known to be increased by cytokines in pancreatic β cells (Kanki et al 2009, Humphrey et al 2010, Kanwar 2010, Quintana-Lopez et al 2013.…”
Section: :3supporting
confidence: 81%
See 2 more Smart Citations
“…This notion is consistent with previous findings that have shown that insulin can increase ROS levels in target cells (Goldstein et al 2005b), probably via the NOX family of NADPH oxidases (Guichard et al 2008), several members of which 230:3 are expressed in pancreatic islets (Guichard et al 2008). Insulin was also reported to induce apoptosis in glucosedeprived β cells (Guillen et al 2008) and potentiate the deleterious effects of H 2 O 2 on β cell survival (Sampson et al 2010). Of special interest in this regard is our finding that insulin increased the expression of iNos and Trb3, factors whose expression is known to be increased by cytokines in pancreatic β cells (Kanki et al 2009, Humphrey et al 2010, Kanwar 2010, Quintana-Lopez et al 2013.…”
Section: :3supporting
confidence: 81%
“…Most studies attribute any deleterious effects of this association to overproduction of insulin by the β cells that eventually results in a classical induction of ER stress, UPR and eventual death of the β cell (Fonseca et al 2011). Although the concentrations used in this study are unlikely to be attained in the blood during hyperinsulinemia, they are in accord with those used in other studies regarding insulin effects on its target tissues (Biswas et al 2007, Guillen et al 2008, Du & Ding 2009. Furthermore, some studies report levels as high as 700-800 pM (Movassat et al 1997, Remington et al 2015.…”
Section: :3supporting
confidence: 76%
See 1 more Smart Citation
“…It was recently reported that insulin has a biphasic effect on b cell survival that appears to depend on glucose level, being pro-apoptotic in glucose-deprived cells [15]. The mechanism of this effect, whether via IR or some other pathway, was not investigated.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, insulin may protect different cells from cell death through activation of a PI3-kinase pathway. It was recently reported that insulin also has a proapoptotic effect on b cells which was dependent on glucose deprivation [15]. Insulin has been shown to induce ROS production in several cell types (see [16], effects of which on cell death may vary.…”
Section: Introductionmentioning
confidence: 99%